2022
DOI: 10.3390/biomedicines10030569
|View full text |Cite
|
Sign up to set email alerts
|

The Proteome of Antibody-Mediated Rejection: From Glomerulitis to Transplant Glomerulopathy

Abstract: Antibody-mediated rejection (ABMR) is the leading cause of allograft failure in kidney transplantation. Its histological hallmark is represented by lesions of glomerulitis i.e., inflammatory cells within glomeruli. Current therapies for ABMR fail to prevent chronic allograft damage i.e., transplant glomerulopathy, leading to allograft loss. We used laser microdissection of glomeruli from formalin-fixed allograft biopsies combined with mass spectrometry-based proteomics to describe the proteome modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 53 publications
(65 reference statements)
0
22
0
Order By: Relevance
“…Also here, WARS1 protein was overexpressed in leucocytes infiltrating the glomeruli as well as in endothelial cells during ABMR 65 . Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3+ T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Also here, WARS1 protein was overexpressed in leucocytes infiltrating the glomeruli as well as in endothelial cells during ABMR 65 . Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3+ T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries.…”
Section: Discussionmentioning
confidence: 54%
“…These three transcripts were previously reported as primary DEGs in bulk transcriptomic analyses of kidney allograft rejection 64 and ABMR 17 . Using microdissection on formalin-fixed kidney allograft biopsies combined with mass spectrometry-based proteomics, it was recently reported that 77 proteins were deregulated in glomerulitis compared to stable grafts, particularly involved in cellular stress mediated by interferons type I and II, leukocyte activation and microcirculation remodeling 65 . Also here, WARS1 protein was overexpressed in leucocytes infiltrating the glomeruli as well as in endothelial cells during ABMR 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). This definition was based on the initial study that revealed these proteins by mass spectrometry, including 21 ABMR and 8 stable graft cases, which was used as a training cohort for the pathologists 13 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we analyzed the glomerular proteome modifications during active ABMR compared to stable grafts, using laser microdissection combined with tandem mass spectrometry 13 . We described 77 dysregulated proteins in glomerulitis and highlighted 3 interferon-related proteins, which displayed an overexpression by immunohistochemistry in glomerular endothelial cells during ABMR: WARS1, TYMP and GBP1.…”
Section: Introductionmentioning
confidence: 99%